"Too different to be accepted, too different to fit in" : adolescent girls' perceptions of living with ASD, as presented on YouTube - Feist, Naomi Anna (My University, 2015)
It is well known that those with autism spectrum disorders (ASDs) have difficulties with social interactions and the forming of meaningful relationships. This difficulty becomes even more pronounced during adolescence when peer relationships and friendships become extremely important for the formation of identity. The way in which these individuals experience these difficulties and make sense of the disorder may be influenced by the views society has regarding their diagnosis and their behavioural differences. This research focused on girls with ASD. Females on the spectrum may present with different symptomology to males, which may further influence their experiences. Sixteen videos of three girls with ASD, who are at the stage of adolescence or emerging adulthood, were selected for the sample. These videos were analysed with regard to how these girls construct this condition on YouTube and experience their differences within Western culture. It was, therefore, a unique study in that it involved the analysis of YouTube videos, which allowed access to these adolescents’ unsolicited opinions. An Interpretative Phenomenological Analysis (IPA) approach to data collection and analysis was adopted to gain an in-depth understanding of their experiences. This approach is applied within a social constructionist paradigm, which provided the epistemological framework for this research. The study focused primarily on views of ASD as a difference (identifying flaws and strengths in ASD), and as a disability (viewing it only in terms of the difficulties associated with it). The results revealed that the way ASD is perceived by individuals with the condition may have an impact on their identity formation and acceptance of the diagnosis during the adolescent and emerging adulthood phase of development. Based on the literature in the field, several hypotheses were developed to explain the findings, which may be of interest for further research. Furthermore, several recommendations are provided to inform therapeutic intervention.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education (Educational Psychology) in the faculty of Humanities, University of the Witwatersrand, Johannesburg, 2013.